Atypical fibroxanthoma of the cheek-case report with dermatoscopy and dermatopathology - Mike Inskip; Jill Maghee; David Weedon; Cliff Rosendahll (Mattioli1885, 2014)
We present a case report of an atypical fibroxanthoma on the cheek of a 73-year-old man. Clinical, dermatoscopic and dermatopathologic images are presented.